Biostratigraphy and paleoecology of an unusual palynological record from the Aquidauana Formation, Late Pennsylvanian of Paraná Basin - Souza, Paulo A.; Perinotto, José A. J. [UNESP]; Félix, Cristina M.; Araújo, Bruno C. [UNESP] (Academia Brasileira de Ciências, 2015)
The Aquidauana Formation is a Permo-Carboniferous sedimentary unit, widely stratigraphicaly distributed in the northwestern and northern portions of the Paraná Basin. However, little paleontological data is available from this formation, preventing accurate biostratigraphic and paleoecological interpretations. An abundant, diversified and well preserved assemblage of palynomorphs was recognized from sampling conducted in an outcrop section in Cipolândia District of Aquidauana Municipality, state of Mato Grosso do Sul, Brazil. A total of 35 indigenous palynomorph taxa was recognized, comprising 6 species of spores (related to 5 genera), 28 species of pollen grains (14 genera) and 1 species of chlorophycean algae. Monosaccate pollen grains are exceptionally dominant, representing 90.38% of the association, particularly constituted by species of the genera Cannanoropollis (30.41% of the total assemblage), Potonieisporites (28.14%) and Plicatipollenites (19.52%). This quantitative overrepresentation is not usual from Gondwana deposits, revealing a particular plant dominance of Cordaitales in the terrestrial flora. These results are interpreted as an upland ecology characterized by plants with a moisture-independent reproduction strategy, under a glacial climate influence. Certain species of pollen allow assignment of this assemblage to the Crucisaccites monoletus Zone (Late Pennsylvanian), which had been recognized only in the middle portion of the Itararé Group at the northeastern margin of the basin.

A Formação Aquidauana é uma unidade sedimentar permocarbonífera, estratigraficamente bem distribuída nas porções norte e noroeste da Bacia do Paraná. Entretanto, poucos dados palinológicos são disponíveis para esta formação, limitando interpretações bioestratigráficas e paleoecológicas acuradas. Uma abundante, diversificada e bem preservada assembleia de palinomorfos foi registrada a partir de uma amostragem de uma seção aflorante realizada no Distrito de Cipolândia, cidade de Aquidauana, Estado do Mato Grosso do Sul, Brasil. Um total de 35 táxons de palinomorfos indígenas foi reconhecido, compreendendo seis espécies de esporos (relacionados a cinco gêneros), 28 espécies de grãos de pólen (14 gêneros) e 1 espécie de alga clorofícea. Grãos de pólen monossacados são excepcionalmente dominantes, representando 90,38% da associação, particularmente constituídos por espécies dos gêneros Cannanoropollis (30.41% do total da assembleia), Potonieisporites (28,14%) e Plicatipollenites (19,52%). Esta super representatividade quantitativa não é usual em depósitos do Gondwana, revelando uma dominância especial das Cordaitales no na flora terrestre. Estes resultados são interpretados como resultante de condições ecológicas caracterizadas por plantas que ocupavam terras altas, com independência de umidade na estratégia de reprodução, sob influência climática glacial. Certas espécies de grãos de pólen permitem posicionamento na Zona Crucisaccites monoletus (Pennsilvaniano tardio), a qual tem sido reconhecida somente na porção média do Grupo Itararé na margem nordeste da bacia.
Keywords: Biostratigraphy; Paleoecology; Palynology; Pennsylvanian; Bioestratigrafia; Paleoecologia; Palino logia; Pennsilvaniano